Time dependence of electrical characteristics during the charge decay from a single gold nanoparticle on silicon. Issue 68 (16th November 2020) - Abbas, Yawar; Rezk, Ayman; Saadat, Irfan; Nayfeh, Ammar; Rezeq, Moh'd
Abstract : In this work, we investigate the time dependence of trapped charge in isolated gold nanoparticles (Au-NPS) dispersed on n-Si substrates, based on the electrical characteristics of nano metal–semiconductor junctions. Abstract : In this work, we investigate the time dependence of trapped charge in isolated gold nanoparticles (Au-NPS) dispersed on n-Si substrates, based on the electrical characteristics of nano metal–semiconductor junctions. The current–voltage ( I – V ) characteristics have been analysed on a single Au-NP at different time intervals, using conductive mode atomic force microscopy (AFM). The Au-NPs have been characterized for their morphology and optical properties using transmission electron microscopy (TEM), ultraviolet visible (UV-vis) spectroscopy and scanning electron microscopy (SEM). The tunneling current is found to be a direct function of the trapped charge in the NP, due to the charge screening effect of the electric field at the NP/n-Si interface. The evolution of the I – V curves is observed at different time intervals until all the trapped charge dissipates. Moreover, the time needed for nanoparticles to restore their initial state is verified and the dependence of the trapped charge on the applied voltage sweep is investigated.